1989
DOI: 10.1111/j.1469-8749.1989.tb03984.x
|View full text |Cite
|
Sign up to set email alerts
|

An Epidemiological Study of Children's Attitudes Toward Disability

Abstract: SUMMARY In this epidemiological study the authors recorded the attitudes of children in Hamilton, Ontario, to physically disabled and mentally handicapped children. Univariate analyses confirmed the importance of female gender, friendship and contact with handicapped persons as determinants of more accepting attitudes. Type of disability and the presence or absence of disabled children in respondents' schools were not found to influence attitudes in a systematic manner. Correlations between attitudes and child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
25
2
30

Year Published

1995
1995
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(62 citation statements)
references
References 20 publications
5
25
2
30
Order By: Relevance
“…The data should also inform us about the way the three evaluative dimensions are used to qualify a child's behavior. (d) In line with what is generally observed (e.g., Bell and Morgan 2000;Cohen et al 1997;Hutzler 2003;King et al 1989;Popovich et al 2003;Siperstein et al 1977;Tervo et al 2002), we predicted that the evaluations of women would be higher on average than those of men.…”
Section: Introductionsupporting
confidence: 54%
“…The data should also inform us about the way the three evaluative dimensions are used to qualify a child's behavior. (d) In line with what is generally observed (e.g., Bell and Morgan 2000;Cohen et al 1997;Hutzler 2003;King et al 1989;Popovich et al 2003;Siperstein et al 1977;Tervo et al 2002), we predicted that the evaluations of women would be higher on average than those of men.…”
Section: Introductionsupporting
confidence: 54%
“…14,16,17,21,22,30,32,[34][35][36][37]40,[45][46][47]49 These studies all showed that the more contact children had with people with disabilities, the more positive their attitudes were towards disability. From the nine articles in which effect sizes were available or calculated, effect size d ranged from 0.17 to 2.45 (Table I).…”
Section: Main Results Of Individual Studiesmentioning
confidence: 99%
“…The CATCH was used in full in four studies, 14,[34][35][36] and a subscale was used in one additional study. 37 The 'Attitudes Towards Disabled Persons' 38 scale, or adapted versions of it, was used in four studies.…”
Section: 32mentioning
confidence: 99%
“…Studies indicate that, despite the Americans With Disabilities Act and other contemporary efforts to integrate individual lives across (dis)abilities, many young Americans still report limited levels of intimate contact with individuals with disabilities (King, Rosenbaum, Armstrong, & Milner, 2008;Rosenbaum, Armstrong, & King, 1986, 1988. Given that "personal contact is a major factor in attitudinal shifts (about disabilities) across many cultures," young peoples' relationships across (dis)abilities stand to affect both the individuals involved and the cultures/societies in which they are embedded (McConkey, Dowling, Hassan, & Menke, 2012, p. 11).…”
Section: Discussionmentioning
confidence: 99%